PERAN GAYA HIDUP DALAM MEMEDIASI PENGARUH DEMOGRAFI TERHADAP NIAT BELI SEPEDA MOTOR VESPA PIAGGIO - Separsa Kusuma, Ida Bagus; Suparna, Gede (E-Jurnal Manajemen; Vol 4 No 8 (2015), 2015)
The purpose of this study was to determine the influence of demographic and lifestyle on purchase intention Piaggio Vespa motorcycle and how the role of lifestyle in mediating the effect of demographics on purchase intention Piaggio Vespa motorcycles. This study used path analysis technique is accompanied by sobel test. The results of this study indicate that demographic variables are positive and significant effect on the lifestyle, demographic and lifestyle variables positive and significant effect on purchase intention Vespa Piaggio motorcycles, as well as lifestyle able to mediate the effect of demographics on purchase intention Piaggio Vespa motorcycles. Lifestyle able to be variable partial mediation, it indicates that lifestyle serves to bridge the influence of demographic variables on purchase intention Piaggio Vespa motorcycles.
Keywords: purchase intention, demographics, lifestyle.